2017
DOI: 10.1002/lary.26909
|View full text |Cite
|
Sign up to set email alerts
|

Malignant fibrous histiocytoma: Database review suggests a favorable prognosis in the head and neck

Abstract: 4. Laryngoscope, 128:885-888, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 18 publications
2
8
0
Order By: Relevance
“…For smaller tumours with no evidence of metastasis, surgical extirpation alone may be the definitive treatment [16,23]. Our study showed that tumour size > 10 cm was a prognostic factor for both poor OS and CSS, which was consistent with a recent study [16].…”
Section: Survival By Tumour Sizesupporting
confidence: 91%
See 1 more Smart Citation
“…For smaller tumours with no evidence of metastasis, surgical extirpation alone may be the definitive treatment [16,23]. Our study showed that tumour size > 10 cm was a prognostic factor for both poor OS and CSS, which was consistent with a recent study [16].…”
Section: Survival By Tumour Sizesupporting
confidence: 91%
“…These tumours can infiltrate adjacent tissues and metastasize distally [13][14][15][16][17][18][19]. However, the outcome and prognosis of patients with MFN of long bones have not been reported because of its rarity.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with tumors that occurred in the extremities, trunk tumors showed no statistically significant difference for OS, LRFS, and MFS in our cohort. However, one report21 showed that tumor located in the head and neck had a favorable prognosis due to a smaller size and a lower grade contrast with Sabesan, who reported that head and neck tumor would have a poor outcome because of the inadequate resection 22. To sum up, the tumor size, grade, depth, or important structures involvement may play a crucial role in patient prognosis.…”
Section: Discussionmentioning
confidence: 98%
“…Head and neck malignant fibrous histiocytoma present at a smaller size and lower grade, likely due to earlier presentation in this region. Because of this, head and neck malignant fibrous histiocytoma represents a favorable survival prognosis compared with extremity disease [65,66].…”
Section: Summary Of Evidencementioning
confidence: 99%